Sustainable product innovation in agri-food industry: Do ownership structure and capital structure matter? - Beatriz Aibar-Guzmán; Isabel-María García-Sánchez; Cristina Aibar-Guzmán; Nazim Hussain (Journal of Innovation & Knowledge (JIK), 2022)
Sustainable product innovation is a key issue facing agri-food companies to maintain and increase their competitiveness. Based on a sample of 320 international agri-food companies for the period 2002-2017, this paper analyzes the role that ownership structure and capital structure play with regard to sustainable product innovation as well as whether these financing decisions differ depending on the firm's ownership structure. The results indicate that family-owned firms show an aversion to this type of eco-innovation projects, regardless of their source of financing. On the contrary, ownership by cross-holdings favors investment in sustainable product innovation projects, showing a greater preference for the use of debt financing versus auto-financing to fund them.
Keywords: G32; M140; O130; Q130; 650; Agri-food sector; Corporate capital structure; Innovation; Ownership structure; Sustainable products